Structural Inequality in International Trade Law: Colonial Legacies and Indonesia’s Legal-Policy Responses - Andri Sutrisno; F.X. Joko Priyono; Nanik Trihastuti; Muhammad Annas (Sriwijaya Law Review, 2026)
Legacies of colonialism remain deeply embedded in the architecture of contemporary international trade, particularly for developing nations such as Indonesia. The legal and institutional framework governing global commerce, largely shaped during the colonial period, continues to generate inequalities in market access, regulatory standards, and participation in global value chains. Indonesia, in particular, continues to grapple with persistent reliance on raw commodity exports, protectionist barriers imposed by advanced economies, and the outsized influence of multinational corporations within key economic sectors. This paper explores how these historical colonial patterns continue to shape Indonesia's contemporary trade policy, alongside the measures the country has adopted to address them—most notably its industrial downstreaming agenda, active engagement in regional and multilateral trade frameworks, and ongoing attempts to renegotiate trade arrangements on more favorable terms. The analysis further situates Indonesia's experience alongside comparable efforts by other developing economies, including Vietnam, Brazil, and South Africa, to confront similar structural constraints. Existing scholarship has generally treated the colonial roots of trade inequality and the domestic policy responses of developing states as separate lines of inquiry, leaving limited systematic connection between historical structural legacies and present-day measures like downstreaming, while cross-country comparisons remain scarce. This study addresses that gap by combining a historical-colonial lens with comparative policy analysis, offering a novel framework linking colonial-era trade structures to the effectiveness of downstreaming and economic diplomacy under current global trade governance underscoring the need for proactive diplomacy and stronger South-South cooperation toward a fairer trading system.